2021
DOI: 10.1177/1754337121995967
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of bilateral and shear components in a two-legged counter-movement jump

Abstract: Strength asymmetry can be detrimental to athlete performance and may lead to injury. The countermovement jump (CMJ) can be used to measure strength asymmetry via shear force production. The reliability of parameters and effects of asymmetry and shear force production on vertical CMJ performance were evaluated in a study with 15 university-level sprint and high jump athletes ( m = 11, f = 4). The athletes performed three CMJs on two occasions, separated by 1 week. Tri-axial ground reaction force (GRF) was recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(53 reference statements)
2
2
0
Order By: Relevance
“…Specifically, all velocity- and COM-related variables were reliable, as well as the duration of the propulsive phase, flight phase, and the ratio between flight time and overall jump time. In line with our study, velocity-related variables were shown to be consistently reliable [ 19 , 21 , 39 ], as well as the COM-related variables (depth of the countermovement and height of the COM at take-off) [ 14 , 19 , 39 ]. However, the results of previous studies are somewhat contradictory when it comes to the reliability of the duration of the different CMJ phases.…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, all velocity- and COM-related variables were reliable, as well as the duration of the propulsive phase, flight phase, and the ratio between flight time and overall jump time. In line with our study, velocity-related variables were shown to be consistently reliable [ 19 , 21 , 39 ], as well as the COM-related variables (depth of the countermovement and height of the COM at take-off) [ 14 , 19 , 39 ]. However, the results of previous studies are somewhat contradictory when it comes to the reliability of the duration of the different CMJ phases.…”
Section: Discussionsupporting
confidence: 87%
“…The results showed a tendency toward decrease in healthy tendon and increase in injured tendon (echo types III and IV), even though we were not able to demonstrate this tendency statistically. The results of this study support previous histological findings proving that tendon structural changes are a response to the load applied [25,26].…”
Section: Discussionsupporting
confidence: 91%
“…The above Table 1 shows the intraclass correlation coefficient (ICC) values for patellar tendon UTC for all echotypes at 20%, 40% and 80% of tendon length. ICC for CMJ is also reported to be a reliable test; however, it was not performed in this study [25]. The descriptive data median, interquartile range (IQR), and coefficient interval percentage at 95% at the first and last day of pre-season and following the first competitive training for healthy and injured tendon at 20%, 40% and 80% tendon length is provided in the Tables A1-A3, as well as in Figure 2.…”
Section: Resultsmentioning
confidence: 97%
“…A variable that should be considered in any injury prediction model is performance asymmetry. An asymmetry (Asym) represents differences between right and left direction and is expressed as a percentage (Gordon et al, 2021 ). Helme et al, did a systematic review of 14 clinical prediction model studies with half of the studies finding statistically significant results.…”
Section: Introductionmentioning
confidence: 99%